Formação repertório e imaginários de docência: gênero e interseccionalidades em um curso de Licenciatura em Química - Machado, Gabriella Eldereti (2022)
This research is part of the Graduate Program in Education at the Federal University of Santa Maria (UFSM), being developed in the Doctorate in Education, in the line of research: Teaching, Knowledge and Professional Development. It counts with the contribution of studies on the Social Imaginary by Cornelius Castoriadis and productions from the Group of Studies and Research in Education and Social Imaginary – GEPEIS of UFSM. Its general objective is to understand the imaginary social meanings in relation to gender issues and intersectionalities in the formative path of four (04) teachers and three (03) students of the Degree in Chemistry at IFFar Campus Alegrete. It adopts the Biographical Method as an investigation path, through the research-training methodology through life narratives, based on the studies of Marie- Christine Josso (2010). Narrative interviews were carried out with the research device called “Deck of Social Imaginary Meanings”, the deck is composed of 17 cards, with the function of provoking the narrative of life through representative words on the central themes of the study. The interviews with the seven (07) study participants were carried out during the year 2021 via virtual meetings on the Google Meet videoconferencing platform due to the global pandemic of COVID-19. With this, it was possible to build the concept of Repertory Formation, with theoretical reference in the studies of Edgar Morin (2000), which made possible the articulation in a spiral sense of themes of gender and intersectionality in dialogue with the knowledge of the specific area of the Chemistry course Graduation. Therefore, we arrive at the final considerations, in which we note the predominance of the conception of gender linked to the biological and binary aspect (male/female), although there is an understanding of the rupture of this biological conception, in the sense of understanding social relations and cultural meanings in the construction of gender. As for the social imaginary meanings of intersectionality, there is a difficulty in understanding the characterizations of the term, even though the participants name the different forms of oppression, such as social class, race, ethnicity and gender.